How did the asset markets change after the Global Financial Crisis? - Kuang-Liang Chang; Charles Ka Yui Leung (Osaka University, Institute of Social and Economic Research (ISER), 2021)
The Global Financial Crisis (GFC) changes the relative economic riskiness and risk-adjusted-performance of different asset markets. While the empirical distribution for stock return shifted to the right and became more concentrated around the mean after the GFC, the real estate market counterparts moved to the left and became more spread out. The economic risk of the OFHEO and Case-Shiller housing indices was smaller than the counterpart of the equity REIT (EREITs) market before the financial crisis, it substantially increased. Also, the economic performance of the OFHEO and Case-Shiller housing indices decreased after the financial crisis. They are below the performance indices of the stock and EREITs markets. The ex-post real estate premium vanishes. If we presume the "best model" to be the same before and after the GFC, we could severely misestimate the risk after the GFC.
Keywords: C50; G32; R30; 330; economic index of riskiness; risk-adjusted-performance index; real estate markets; stock markets